Comparative sensitivity of 1, 3 beta‐D‐glucan for common causes of candidaemia in South Africa. Issue 11 (2nd September 2019) - Chibabhai, Vindana; Fadana, Vuyolwethu; Bosman, Norma; Nana, Trusha
Summary: Culture‐based diagnosis of candidaemia suffers poor sensitivity and prolonged turnaround time. The 1, 3‐beta‐D‐glucan (BDG) assay is a non‐culture‐based broad fungal antigen with rapid turnaround time. To assess overall, species‐specific and population‐specific sensitivity of the BDG assay for candidaemia, to determine if the BDG assay is able to detect candidaemia prior to blood culture collection, and to evaluate the performance of the assay for the detection of Candida auris candidaemia. A retrospective review of all blood cultures (BC) with C albicans, C parapsilosis, C glabrata, C krusei and C auris was performed. A corresponding BDG result (Fungitell ® ) within 10 days of the BC was sought on the laboratory information system. Overall sensitivity of the assay was 79% (95% CI 73‐85; 173/218). Per species sensitivity was 81% (95% CI 72‐90; 66/81) for C albicans, 72% (61‐83; 60/83) for C parapsilosis, 90% (95% CI 79‐100; 27/30) for C glabrata, 71% (95% CI 43‐99; 10/14) C auris and 100% (10/10) for C krusei . No statistically significant difference in sensitivity between species was noted ( P = .093). The assay demonstrated 92% (59/64) sensitivity in neonatal ICU ( P = .047) compared to 94% (15/16) in surgery, 81% (59/73) in adult ICUs and 71% (15/21) in Oncology. BDG results were positive up to 10 days prior to blood culture collection with no significant difference in detection rate ( P = .563). BDG results were positive up to 10 days prior to blood culture collection. BDG when collected a mean of 2.5 days (range 1‐10 days) prior to blood culture collection were positive.